Analisis Unsurfaced Road Condition Index Untuk Kualitas Jalan Tambang PT Antareja Mahada Makmur Kalimantan Timur: Analysis of Unsurfaced Road Condition Index for the Quality of Mining Roads of PT Antareja Mahada Makmur East Kalimantan - Halimatussa’diah, Nasyitha; Razak, Supardi; Budiono, Agus (CV Insight Publisher, 2023)
Overburden stripping is a process of removing overburden to extract the underlying minerals, and is an activity in the early stages of mining. A company that carries out mining activities must carry out stripping activities. The purpose of this study is to analyse the quality of haul roads using the URCI and CBR methods, analyse the obstacles that occur to provide recommendations for improvement, and provide recommendations for the thickness of road layers for overburden haul roads. The research method used is a quantitative method. Road geometry consists of straight road width, bend road width, road slope, superelevation and also crossfall. Based on the test results with the help of dynamic cone penetrometer test, it is known that the CBR value of 6 test points obtained values of 67.5, 42, 59.25, 70.90, 50 and 60, where the limit of good condition of a road based on percent CBR is 55 so that there are 2 roads that are not in good condition. Based on observations using the URCI method with 7 parameters, a value of 65 was obtained for 2 observation locations. Based on the observation results, it is known that in the three rock samples that have been soaked in water for three days, it is known that the material contained in HEX4035 is a material that dissolves quickly in water, resulting in mud. Meanwhile, the material in the mining front of HEX4036 and HEX1440 does not dissolve quickly in water so that the material can be a material for road layers as high as 9 inches for sub base and 7 inches for surface course.